ANTI ACNE ACTIVITY OF ACETONE EXTRACT OF PLUMBAGO INDICA ROOT - KAUR, DARSHPREET; Prasad, Shyam Baboo (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Acne is the most common disorder of skin. Approximately 85 % of all adolescents suffer from acne and 30% of them used pharmaceutical however remaining population rely on traditional medicine for cure of acne. In present study an attempt has been taken to investigate the in vitro anti‑acne activity of acetone extract of root of Plumbago indica. The antiacne activity was investigated against two acne causing bacteria, i.e., Propionibacterium acne and Staphylococcus epidermidis and yeast Malassezia furfur by well diffusion method. The result showed that drugs was active against all microorganism. The Minimum inhibitory concentration of the P. indica root extract against test P. Acne, S. Epidermidis and M.furfur was found to be 600µg/ml, 200 µg/ml and 300µg/ml respectively. However the extract acts in dose dependent manner against causative microorganism.Result suggests that P.indica has potential activity against acne causing microorganism and hence this can be used in topical anti‑acne preparations. Key words: Plumbago indica, Acne, Propionibacterium acnes, Staphylococcus epidermidis, Malassezia furfur, Skin disorder.